Identifikasi Loyalitas Pelanggan dengan Kepuasan Sebagai Variabel Intervening Pada Toko Grosir HR Losari Kecamatan Cilongok Kabupaten Banyumas - Sulasih, Sulasih; Parno, Parno; Trianingsih, Ade; Intansari, Anggita Isty (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This study aims to determine whether product diversity, perceived value, and location have an effect on customer loyalty with customer satisfaction as a mediating variable at the HR Losari Wholesale Store, Cilongok District, Banyumas Regency. The quantitative research method and analysis tool used in this study are Smart-PLS 4. The sample collection method uses non-probability sampling with a purposive sampling technique so that 385 respondents are produced. The results of this study indicate that perceived value and location have a significant effect on customer loyalty with strong validity and reliability tests. However, product diversity does not have a significant effect on customer loyalty. Product diversity, perceived value, and location have a significant effect on customer satisfaction. The intervening variable of customer satisfaction can also mediate the relationship between Product diversity, perceived value, and location on customer loyalty